Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1073/pnas.90.21.9818
|View full text |Cite
|
Sign up to set email alerts
|

Subunit structure of a class A aspartate transcarbamoylase from Pseudomonas fluorescens.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…The class A ATCases are large-molecular-mass enzymes (470 to 600 kDa) that were thought to be dimeric until Bergh and Evans (3) showed that the Pseudomonas fluorescens enzyme exists as a trimer with a 34-kDa catalytic chain in a dodecameric association with a 45-kDa chain of unknown origin and function. Similar results from studies with purified protein have been obtained by Shepherdson and McPhail (38) for the ATCase from Pseudomonas syringae.…”
mentioning
confidence: 99%
“…The class A ATCases are large-molecular-mass enzymes (470 to 600 kDa) that were thought to be dimeric until Bergh and Evans (3) showed that the Pseudomonas fluorescens enzyme exists as a trimer with a 34-kDa catalytic chain in a dodecameric association with a 45-kDa chain of unknown origin and function. Similar results from studies with purified protein have been obtained by Shepherdson and McPhail (38) for the ATCase from Pseudomonas syringae.…”
mentioning
confidence: 99%
“…An explanation for this could be that the catalytic and non- catalytic subunits dissociate very readily in these species, although we regard this as unlikely in view of the known stable binding of the two types of subunit in the fluorescent pseudomonads (Bergh & Evans, 1993 ;Shepherdson & McPhail, 1993). We have tried to exclude the possibility that the 100 kDa enzymes identified in this study are dissociation products of class A or class B ATCases.…”
Section: Discussionmentioning
confidence: 97%
“…The reasons for purifying this enzyme were similar. It has been shown that three fluorescent pseudomonads have ATCases with molecular mass values in the 480 kDa region and are constructed from polypeptides of around 34 and 45 kDa (Bergh & Evans, 1993 ; organisms within these groups. One such cluster-in the y-3 group is the fluorescent pseudomonads, the acinetobacters, the xanthomonads, S. maltophilia and lysobacters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations